Wastewater Management as a Part of Solution for Water Resources Problem in Erbil City - Bahar Ahmed; Shuokr Qarani Aziz; Sarwah Othman Ismael; Kasro Kakil Dizayee (Zanco Journal of Pure and Applied Sciences, 2024)
In Erbil City, municipal wastewater (MWW) is disposed directly without any treatment processes in the natural environment water body and in some places used for irrigation purposes. Untreated MWW causes problems for the environment, and people's health. Water quantity and quality variation produce complications for water sources in Erbil City, Kurdistan Region-Iraq. There is a lack of performing MWW management fundamentals in the area as well. This research aimed to study the MWW management in Erbil City, presenting water resource difficulties and bringing about suitable solutions for the water resource problems, and also to highlight the risk for the poor Management. MWW Data on Erbil municipal (EMWW) water quality parameters were collected and analyzed for the study period (four months), beginning in October 2022 and ending in March 2023. Twelve EMWW quality parameters were captured and tested in the Laboratory, arranged, and compared with MWW disposal criteria and local standards. The following MWW parameters include pH, electrical conductivity (EC), total dissolved salts (TDS), chloride (CL), total solids (TS), total alkalinity, total acidity, chemical oxygen demand (COD), and colour. The results showed that Erbil's MWW characteristics in terms of temperatures ranged between 11-23 °C and in turn, affected biological species activities. Maximum PH value was 7.7. Total alkalinity found in the range from 140 to 178 mg/l. Chloride concentration results showed for October was 62 mg/l and the maximum value was 80 mg/l in November due to the increment in temperature and evaporation. The range of the COD values of sewage water for five months was 246 -773 mg. Erbil's MWW's moderate to medium strength may be treated and utilized for landscaping, fountains, and irrigation, minimizing the need for fresh water from resources like wells and surface water in the Greater Zab River.